Forensic and pharmaceutical problems concerning circulation of cannabis: perspectives of state control, medical and narcological health effects - Shapovalova, Viktoriya; Shapovalov, Valeriy; Negretsky, Serhiy (Actual Problems of Medicine and Pharmacy, 2021)
Based on the experience of the Netherlands proposed removal of cannabis from illegal circulation and prospects are state control.